2021
DOI: 10.3389/fcell.2021.760532
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans and Glycosaminoglycans in Stem Cell Homeostasis and Bone Tissue Regeneration

Abstract: Stem cells maintain a subtle balance between self-renewal and differentiation under the regulatory network supported by both intracellular and extracellular components. Proteoglycans are large glycoproteins present abundantly on the cell surface and in the extracellular matrix where they play pivotal roles in facilitating signaling transduction and maintaining stem cell homeostasis. In this review, we outline distinct proteoglycans profiles and their functions in the regulation of stem cell homeostasis, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 182 publications
0
21
0
Order By: Relevance
“…2 D). This result highlights a first change that could interfere with the proliferation and differentiation capacity of BM-MSCs ( Chen et al, 2021 ). Of note, AGEs were detected but with no difference between the two types of ECM BMAd (data not shown).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…2 D). This result highlights a first change that could interfere with the proliferation and differentiation capacity of BM-MSCs ( Chen et al, 2021 ). Of note, AGEs were detected but with no difference between the two types of ECM BMAd (data not shown).…”
Section: Resultsmentioning
confidence: 82%
“…First, these results seem surprising in light of several factors secreted by BMAds that can inhibit osteoblastogenesis ( Rharass and Lucas, 2018 ) and could be retained by the ECM. Second, the ECM composition itself is expected to modify BM-MSC commitment and differentiation ( Hoshiba et al, 2016 ), and the change in GAG content between the two ECM BMAds could have modulated the cell response ( Chen et al, 2021 ). However, another independent study reported that the ECM generated after either early or later stages of adipogenesis (3 and 10 days, respectively) does not perturb osteoblastogenesis: human BM-MSC-derived osteoblasts differentiated either on these adipocyte ECMs or osteoblast ECM display similar ALP staining and RUNX2 and OPN mRNA expression ( Hoshiba et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the Jagged1-activated Notch signaling pathway participated in several gene expression and translational processes of ECM proteins. The potentiality of proteoglycans and GAGs in facilitating biological processes of stem cells was previously reported, which is a promising tool for developing as a bioactive material in bone regeneration ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Cell and Developmental Biology frontiersin.org proteoglycans and GAGs in facilitating biological processes of stem cells was previously reported, which is a promising tool for developing as a bioactive material in bone regeneration (Chen et al, 2021). Characterization of dental pulp stem cells in the Jagged1knockout mouse model is not achievable due to embryonic lethality (Xue et al, 1999).…”
Section: Figurementioning
confidence: 99%
“…These GAGs were visualized between the trabecular-like structures (Figure S7). Although the origin of these GAGs is unclear, they have been shown to inhibit collagen degradation by osteoclastic cathepsin K, promote osteogenic differentiation and bone-like matrix formation, and promote mineralization [53][54][55][56] .…”
Section: In Vitro Remodeling Of Mineralized Silk Fibroin Scaffoldsmentioning
confidence: 99%